Altered expression of microRNA-23a in psoriatic arthritis modulates synovial fibroblast pro-inflammatory mechanisms via phosphodiesterase 4B. (January 2019) - Wade, Sarah M.; Trenkmann, Michelle; McGarry, Trudy; Canavan, Mary; Marzaioli, Viviana; Wade, Siobhan C.; Veale, Douglas J.; Fearon, Ursula
Abstract: Objectives: To investigate the functional role of miR-23a in synovial fibroblasts (SFC) activation in psoriatic arthritis (PsA). Methods: Differential expression of the miR-23a-27a-24-2 cluster was identified by real-time quantitative PCR in PsA synovial tissue and peripheral blood mononuclear cells (PBMC) compared to osteoarthritis (OA) and correlated with disease activity. For regulation experiments, PsA synovial fibroblasts (SFC) were cultured with Toll-like receptor (TLR) ligands and pro-inflammatory cytokines. PsA SFC were transfected with a miR-23a inhibitor to assess the functional effect on migration, invasion and expression of pro-inflammatory meditators. The direct interaction between miR-23a and predicted target mRNA, phosphodiesterase 4B (PDE4B), was examined by luciferase reporter gene assay, with the expression and regulation confirmed by RT-PCR and western blot. A PDE4 inhibitor was used to analyse the function of PDE4B signalling in both miR-23a and Poly(I:C)-induced PsA SFC activation. Results: Synovial tissue expression of miR-23a was lower in PsA compared to OA and correlated inversely with disease activity and synovitis. TLR activation via Poly(I:C) and LPS, but not Pam3CSK4, significantly decreased miR-23a expression, with no significant effect observed in reponse to stimulation with pro-inflammatory cytokines. Decreased miR-23a expression enhanced PsA SFC migration, invasion and secretion of IL-6, IL-8, MCP-1, RANTES and VEGF. We identified PDE4B as a direct target of miR-23a and demonstrated enhanced mRNA and protein expression of PDE4B in anti-miR-23a transfected PsA SFC. Poly(I:C) and/or miR-23a-induced migration and enhanced cytokine expression was suppressed by the blockade of PDE4 signalling. Conclusions: In PsA, dysregulated miR-23a expression contributes to synovial inflammation through enhanced SFC activation, via PDE4B signalling, and identifies a novel anti-inflammatory mechanism of PDE4 blockade. Highlights: miR-23a is decreased in PsA synovial tissue and correlates with disease activity. Joint expression of miR-23a is regulated by TLR3 and TLR4 activation. Decreased expression of miR-23a induces synovial fibroblast activation. miR-23a directly targets PDE4B, which is increased in PsA synovial tissue. PDE4 blockade inhibits miR-23a-induced synovial fibroblast activation.